Diagnostic Accuracy of Serum Prostate Specific Antigen and Gleason Score in Determining the Presence of Skeletal Metastasis in Prostate Cancer Patients: a Pakistani Perspective - Nasir, Taimoor; Aamer, Syeda Neha; Waqar, Saman; Omer, Wafa (Journal of Rawalpindi Medical College, 2023)
Objective: To determine the cut-off values for serum Prostate Specific Antigen and Gleason score for predicting bone metastasis of Prostate cancer. Methodology: This diagnostic accuracy study was conducted in Pakistan Institute of Medical Sciences (PIMS), Islamabad from 2015 to 2018. 330 patients of Prostate cancer were enrolled in the study. Prostate Specific Antigen (PSA) and Gleason Scores (GS) were determined using commercially available ELECSYS® assays in the Modular Analytics E170 (Roche Diagnostics) and histopathology respectively. Tc99m methylene diphosphonate (MDP) was used to perform the Bone scan. Any correlation between these variables was nvestigated to determine a cut-off value for PSA and GS. Results: Out of the total 330 patients included in the sample, BS was positive for metastasis in 186 (56.4%) patients and negative in 144 (43.6%) patients. Amongst these 186 positive patients, 5 (2.7%) had PSA < 20 ng/ml, 174 (93.5%) had PSA between 20 and 90 ng/ml, and 9 (4.8%) had PSA > 90 ng/ml. Out of the 144 patients with negative BS, 142 (98.6%) had PSA < 20ng/ml. Only 2 (1.4%) had PSA in the range of 20 and 90 ng/ml, while none had PSA > 90 ng/ml. In the 147 patients with PSA < 20 ng/ml, 142 (96.6%) did not have any skeletal metastases. Of the 183 patients with PSA > 20 ng/ml, 181 (98.9%) had positive bone scans. Using a cut-off value of 20 ng/ml for serum PSA, 142 unnecessary scans would have been unnecessary. Out of the 186 patients with positive bone scan (BS), 3 (1.6%) patients had GS < 7, 160 (86.0%) patients had GS between 7 and 9, and 23 (12.4%) patients had GS > 9. Out of the 144 patients with negative BS, 84 (58.3%) had GS < 7, 60 (41.7%) had GS between 7 and 9, and none of the patients had a GS more than 9. Of the 87 patients with GS < 7, 3 (3.4%) patients had a positive BS while 84 (96.6%) patients had a negative BS. Of the 243 patients with GS > 7, 183 (75.3%) had a positive BS while 60 (24.7%) patients had a negative GS. These results indicate that a GS > 7 cannot be reliably used to rule in the need for a BS in patients with Prostate cancer. Conclusion: Our study reports that serum PSA < 20 ng/ml can be safely used to omit a bone scan. It also suggests that Gleason Score < 7 nullifies the need to conduct a bone scan. However, serum PSA is a better and more reliable indicator of bone metastases as it has better sensitivity and specificity values as compared to GS. If these results are applied in hospitals all over the country, we can significantly reduce the burden on our resources and prevent unnecessary, low-yield diagnostic tests from being carried out.